2022
DOI: 10.1136/bmjoq-2022-001819
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals’ perception of safety culture and the Operating Room (OR) Black Box technology before clinical implementation: a cross-sectional survey

Abstract: IntroductionComprehensive data capture systems such as the Operating Room Black Box (OR Black Box) are becoming more widely implemented to access quality data in the complex environment of the OR. Prior to installing an OR Black Box, we assessed perceptions on safety attitudes, impostor phenomenon and privacy concerns around digital information sharing among healthcare professionals in the OR. A parallel survey was conducted in Canada, hence, this study also discusses cultural and international differences whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Up to 50% of perioperative adverse events are considered preventable, which makes the occurrence of adverse events a systemic issue. [32][33][34][35][36][37] Implementation of incident reporting systems with feedback loops to the hospital institutions and bodies responsible for external inspection or accreditation of the healthcare services is reckoned a key effort to reduce the number of adverse events, and this is mandatory in Norwegian hospitals. Health professionals are expected to report adverse events through these systems, and managers are required to do comprehensive follow-up analysis to reveal potential embedded risks and thereby contribute to prevent similar events.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%
See 1 more Smart Citation
“…Up to 50% of perioperative adverse events are considered preventable, which makes the occurrence of adverse events a systemic issue. [32][33][34][35][36][37] Implementation of incident reporting systems with feedback loops to the hospital institutions and bodies responsible for external inspection or accreditation of the healthcare services is reckoned a key effort to reduce the number of adverse events, and this is mandatory in Norwegian hospitals. Health professionals are expected to report adverse events through these systems, and managers are required to do comprehensive follow-up analysis to reveal potential embedded risks and thereby contribute to prevent similar events.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%
“…Several studies have demonstrated that adverse events rates among hospitalised patients remain high despite significant efforts to improve quality and safety. Up to 50% of perioperative adverse events are considered preventable, which makes the occurrence of adverse events a systemic issue 32–37. Implementation of incident reporting systems with feedback loops to the hospital institutions and bodies responsible for external inspection or accreditation of the healthcare services is reckoned a key effort to reduce the number of adverse events, and this is mandatory in Norwegian hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Installing cameras to monitor operations is becoming more commonplace with the use of ‘operating room black boxes’, but it is possible that such initiatives could result in resistance. In a cross-sectional survey of Danish healthcare professionals [ 88 ], on average, opinions toward using a black box were neutral or positive, with little concern over data safety. Conversely, in a similar study conducted in Canada [ 89 ], there were more significant concerns over data safety and the potential for litigation, highlighting the importance of considering any concerns within a societal, cultural and legislative context.…”
Section: Introductionmentioning
confidence: 99%
“…The Operating Room Black Box (ORBB) allows direct observation and continuous recording of the intraoperative technical as well as non-technical data; this allows a detailed analysis of efficiency, safety and adverse events. 1 It also acts as a teaching tool in surgical training as it may be used to provide feedback to trainees. Surgeons, thereby increasing transparency in the operating room and improving patient safety.…”
Section: Introductionmentioning
confidence: 99%